DISTRIBUTION CHARACTERISTICS OF FERRO-TITANIUM OXIDE MINERAL ON LOW-GRADE IRON SAND - Suratman Suratman (Puslitbang tekMIRA, 2017)
Iron sand is known as one of the sources of TiO2 in the form of ilmenite or titanomagnetite mineral. Iron-titanium oxide mineral contained in Indonesia iron sand are classified as titanomagnetite. Indonesia possesses a lot of iron sand deposits such as at southern coast of Cilacap, Kebumen and other areas. The iron sand consists of magnetic and non-magnetic minerals as either loses or bound materials. Fractionation of Cilacap iron sand which employed three types of sieve (40, 60 and 80 meshes) showed that the iron sand is dominant in -40+60 fraction (68.38 g) while the most amount of iron and titania contents occurred at fraction of -80 mesh, namely 11.62 and 1.46%. Magnetic separation showed that the finer the particles and the higher the magnetic intensity, the higher the derived iron and titania. The process has also successfully increased the TiO2 content more than 5 times, from 0.325 to 1.67%.